Business process reengineering of drugs storage and distribution: a case study. (1st January 2015) - Bertolini, Massimo; Bevilacqua, Maurizio; Ciarapica, Filippo Emanuele; Postacchini, Leonardo
This works reports on the application of business process reengineering (BPR) methods to drugs management and distribution in an Italian province. The aim of the study was to analyse the process as it was always implemented up until the year 2012, identifying any related problems and inconsistencies, and then describe the reengineering of this process, assessing and emphasising the changes involved and pinpointing further opportunities for improvement. Two To-Be scenarios have been analysed: 1) development of trans-shipment procedure between hospitals; 2) design and use only a centralised warehouse for drug storage and distribution. Processes were modelled using the AI0 WIN software, which supports the IDEF0 method. The main contribution of the IDEF0 application in drug management is to provide a clear view of the whole system, a communication system between hospital actors, a rich information source and a structured base for the reengineering process.